2017
DOI: 10.1557/adv.2017.505
|View full text |Cite
|
Sign up to set email alerts
|

Growth of NbO2 by Molecular-Beam Epitaxy and Characterization of its Metal-Insulator Transition

Abstract: Thin films of NbO 2 are synthesized by oxide molecular-beam epitaxy on (001) MgF 2 substrates, which are isostructural (rutile structure) with NbO 2 . Two growth parameters are systematically varied in order to identify appropriate growth conditions: growth temperature and the partial pressure of O 2 during film growth. θ-2θ X-ray diffraction measurements identify two dominant phases in this system at background oxygen pressures in the (0.2-6)×10 -7 Torr range: rutile NbO 2 is favored at higher growth temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…5,[13][14][15] For lateral resistive switching devices, NbO2 layers with an in-plane [001] direction have been demonstrated. 14,16 However, low room-temperature resistivity values of only several Ωcm [17][18][19][20] have been reported for thin-films so far compared to the intrinsic resistivity value of 10 kΩcm measured for bulk crystals. 21,22 To improve the resistivity ratio at the MIT for thin-film devices, thus, higher room-temperature resistivity is desirable.…”
mentioning
confidence: 99%
“…5,[13][14][15] For lateral resistive switching devices, NbO2 layers with an in-plane [001] direction have been demonstrated. 14,16 However, low room-temperature resistivity values of only several Ωcm [17][18][19][20] have been reported for thin-films so far compared to the intrinsic resistivity value of 10 kΩcm measured for bulk crystals. 21,22 To improve the resistivity ratio at the MIT for thin-film devices, thus, higher room-temperature resistivity is desirable.…”
mentioning
confidence: 99%
“…Thermal and electric conductivity data were extracted from: brain tissue elements, [133] VO 2 , [220] V 2 O 3 , [152,227] NbO 2 . [228,229] The thermal and electrical conductivity of PCMs in the crystalline phase differs from their respective values in the amorphous phase. We consider representative oxides such as, amorphous (a-HfO x ) and crystalline (c-HfO x ) hafnium oxide at room temperature; [147,[230][231][232] amorphous (a-TaO x ) and crystalline (c-TaO x ) tantalum oxide; [145,233] and amorphous (a-TiO x ) and crystalline (c-TiO x ) titanium oxide.…”
Section: Thermoelectric Controlmentioning
confidence: 99%
“…LaCoO 3 may also exist in the oxygen-deficient stoichiometry of LaCoO 3−δ , where 0 < δ < 0.5 (see Figure ). Hitherto, in the LaCoO 3 and La 0.7 Sr 0.3 CoO 3 films, the MIT is a well-observed phenomenon. The studies reported so far state that in LaCoO 3 , the ground state consists of only Co 3+ ions specifically in the 3d 6 spin configuration. At low temperatures (below 50 K), it remains in the LS state, i.e., S = 0 (t 2g 6 e g 0 ).…”
Section: Introductionmentioning
confidence: 99%